2015
DOI: 10.1124/jpet.114.222299
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Biogenic Amine Transporters 15. Identification of Novel Allosteric Dopamine Transporter Ligands with Nanomolar Potency

Abstract: Novel allosteric modulators of the dopamine transporter (DAT) have been identified. We have shown previously that [N-(diphenylmethyl)-2-phenyl-4-quinazolinamine], SRI-20040 [N-(2,2-diphenylethyl)-2-phenyl-4-quinazolinamine], and SRI-20041 [N-(3,3-diphenylpropyl uptake inhibitors: 1) full-efficacy agents with a one-site fit, 2) fullefficacy agents with a two-site fit, and 3) partial-efficacy agents with a one-site fit-the focus of further studies. These agents partially inhibited DA, serotonin, and norepine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…Further studies are needed to elucidate the specific contribution from the two binding sites to the measured affinity of compound 3. Due to the lack of consensus for quantitative determination of the allosteric potency, it is difficult to directly relate our findings to previous reports on SERT binding compounds possessing allosteric properties (Nandi et al, 2004;Nightingale et al, 2005;Kortagere et al, 2013;Rothman et al, 2015). We have previously attempted to produce high-affinity allosteric ligands for SERT (Banala et al, 2013), but none of them showed a notable loss in S1 affinity and, thus, did not show an S2: S1 affinity ratio comparable with the compounds reported herein.…”
Section: Figurementioning
confidence: 54%
See 1 more Smart Citation
“…Further studies are needed to elucidate the specific contribution from the two binding sites to the measured affinity of compound 3. Due to the lack of consensus for quantitative determination of the allosteric potency, it is difficult to directly relate our findings to previous reports on SERT binding compounds possessing allosteric properties (Nandi et al, 2004;Nightingale et al, 2005;Kortagere et al, 2013;Rothman et al, 2015). We have previously attempted to produce high-affinity allosteric ligands for SERT (Banala et al, 2013), but none of them showed a notable loss in S1 affinity and, thus, did not show an S2: S1 affinity ratio comparable with the compounds reported herein.…”
Section: Figurementioning
confidence: 54%
“…Indeed, it has been suggested that the faster onset of action and higher efficacy of S-CIT compared with the racemic mixture is due to its allosteric action at the transporter (Mørk et al, 2003;Sanchez et al, 2004;Storustovu et al, 2004;Sanchez, 2006;Mansari et al, 2007). Other compounds with no apparent similarity to citalopram also possess allosteric properties for SERT (Rothman et al, 2015;Nightingale et al,…”
Section: Discussionmentioning
confidence: 99%
“…This pharmacological class includes therapeutic agents, abused drugs, and experimental compounds, and these drugs can function either as selective DAT inhibitors [e.g., GBR-12935 (1-[2-(diphenylmethoxy)ethyl]-4-(3-phenylpropyl)piperazine)] or as nonselective inhibitors of multiple monoamine transporters (e.g., cocaine) (Matecka et al, 1996). Recently, a new type of DAT inhibitor was identified that differs from prototype DAT inhibitors in three ways (Pariser et al, 2008;Rothman et al, 2015). Specifically, prototype DAT inhibitors like cocaine and GBR-12935 have similar potencies and high efficacies to block 1) extracellular-to-intracellular monoamine transport (i.e., monoamine uptake), 2) intracellular-toextracellular monoamine transport (i.e., amphetamine-induced monoamine efflux), and 3) binding to the DAT orthosteric binding-site labelled by radioligands such as [ 3 H]WIN35428.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of this study was to evaluate the abuse-related behavioral and neurochemical effects produced in rats by SRI-31142 [2-(7-methylimidazo[1,2-a]pyridin-6-yl)-N-(2-phenyl-2-(pyridin-4-yl)ethyl)quinazolin-4-amine] (Fig. 1), one compound from this new class of putative allosteric DAT inhibitors (Rothman et al, 2015). Similar to other compounds in this series, SRI-31142 has nanomolar potency but only partial efficacy to block monoamine uptake via all three transporters [i.e., DAT; serotonin (5-HT) transporter (SERT); norepinephrine transporter (NET)] in rat brain synaptosomes, 1000-fold weaker potency to block [ 3 H]WIN35428 DAT binding, and no efficacy to block amphetamine-induced DAT-mediated monoamine efflux.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular determinants of MAT substrate versus inhibitor binding sites have been investigated using site-directed mutagenesis, computer-aided molecular modeling, and crystallographic techniques. In addition to the substrate binding site, these studies have revealed the presence of additional ligand attachment sites within MATs of which the location and functional relevance remain unknown (Coleman, Green, & Gouaux, 2016, Koldso et al, 2015, Mortensen & Kortagere, 2015, Rothman et al, 2015. The MATs mediate a rapid uptake of neurotransmitters (turnover rate ß1 molecule/sec) from the Figure 12.17.1 Membrane topology of 12-transmembrane (TM) structure (numbered from I to XII) of MATs with intracellular location of N-and C-termini.…”
Section: Introductionmentioning
confidence: 99%